Pengembangan Video Pembelajaran Video Animasi Berbasis Canva “CAKPRA” tentang Keteladan Perjuangan Rasulullah pada Pembelajaran PAI Kelas 5 SD - Ratu, Dinastiara Camila; Safitri, Novia Hani; Azzahra, Ratih Fatimah; Aeni, Ani Nur (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This article describes the use of the animated video "CAKPRA" (Cahaya Exemplary Struggle of the Messenger of Allah), a learning media created to provide more understanding of grade 5 elementary school students, especially in the material of Islamic Religious Education, namely the Hudaibiyah Agreement or Fathu Makkah. This media is interesting because it provides learning material about the Prophet's struggle in conquering the city of Makkah which is packaged in animated videos. This article aims to develop interactive learning media in the form of animated video "CAKPRA" which can help teachers in delivering material Islamic Religious Education in elementary school. The method used is Design and Development (D&D) with the ADDIE model. The trial was conducted on grade 5 students at SDN 2 Jagapura Wetan. The results showed that the video animation "CAKPRA" was effective in improving students' understanding of the Hudaibiyah Agreement or Fathu Makkah. This study also obtained positive responses from students during the learning process. Thus, animated video "CAKPRA" can be used as an alternative learning tool interactive and efficient in order to improve student understanding.